СИМБИОЗ РЕАЛИЗМА И ПОСТМОДЕРНИЗМА В МОЛОДЁЖНОЙ ЛИТЕРАТУРЕ ВЕЛИКОБРИТАНИИ XX ВЕКА (Eurasian Journal of Philology Science and Education, 2015)
Literary process in Great Britain is determined not only by binding of realism, nonrealism and postmodern literature. A lot of adjoining phenomena appeared on the stage must be taken into account by literary men of modern times. Symbiosis of these directions is real fact that has already beenapproved.